Penanaman Modal Asing Di Indonesia - Cahyo Adhi Nugroho; Sri Purwaningsih (PSHPM Untag Semarang, 2025)
This research examines the legal framework and implementation of Foreign Direct Investment (FDI) in Indonesia within the context of national development. The primary issue addressed is the distinction between direct and indirect investment and the legal requirements for foreign entities operating within the Republic of Indonesia. Using a normative judicial approach with descriptive analysis, the study gathers data from primary legal sources, including the 1945 Constitution, Law No. 25 of 2007, and Law No. 40 of 2007. The findings indicate that FDI must generally take the form of a Limited Liability Company (PT) under Indonesian law. Successful investment realization depends on legal certainty, bureaucratic efficiency, and a conducive business climate. The research concludes that while direct investment requires a physical presence and risk-bearing by the investor, indirect investment focuses on short-term capital gains through the capital market. The implication is that Indonesia must maintain stability, predictability, and fairness in its investment regulations to remain competitive in the global economy and the ASEAN Economic Community.